PEMBERDAYAAN MASYARAKAT DALAM PENCEGAHAN STRESS MELALUI TEKNIK RELAKSASI DI LINGKUNGAN DESA BIRU-BIRU - Ansela, Rasninta Devi; Silalahi, Rini Debora; Mutia, Maulidina; Bukit, Herawati (INSTITUT KESEHATAN DELI HUSADA, 2025)
Stress is a common mental health issue experienced by rural communities due to economic pressures, workload, and social dynamics. Limited knowledge and coping skills make individuals more vulnerable to psychological problems. This Community Service Program (PKM) aims to empower the community through education and relaxation technique training as a strategy to prevent stress. The methods included health education, demonstration of deep breathing and progressive muscle relaxation techniques, and guided independent practice. The results showed an 85% increase in participants’ knowledge and a 78% improvement in relaxation skills. This program successfully enhanced community awareness regarding stress management and provided practical skills that can be applied independently. In conclusion, community empowerment through relaxation training is effective in supporting community-based stress prevention.